Mapping and analysis of anticipatory action initiatives in Senegal and Zambia - Nur, L.; Amarnath, Giriraj (International Water Management Institute, 2023)
The frequency and severity of extreme weather events are presenting substantial challenges to communities and nations worldwide. The already escalating impact of climatic hazards is expected to persist due to ongoing climate change. While strides have been made in enhancing forecasting capabilities and establishing early warning systems, global coverage remains inadequate, with just 40% of African countries reporting a multi-hazard early warning system in place as of 2022. Even where forecasting and early warning systems are in place, the translation of early warnings into timely action remains a persistent challenge, as exemplified by past cases of delayed response to imminent disasters.